PENGARUH KOMPETENSI, FASILITAS DAN MOTIVASI TERHADAP KINERJA GURU SMA NEGERI DI KABUPATEN KOLAKA - Meylani Meylani; Ramlawati Ramlawati (AkMen JURNAL ILMIAH, 2017)
The purpose of this research is (1) to analyze the influence of competence to the performance of SMA SMA teacher in Kolaka regency, (2) to analyze the effect of facilities on the performance of high school teacher in Kolaka regency, and (3) to analyze the influence of motivation on the performance of high school teacher in Kolaka District. The method of analysis used in this research is Multiple Regression analysis method. Research data obtained from the teacher. State Senior High School in Kolaka District. The research approach is a causal approach that is explanatory. The results of this study indicate that: (1) competence has a positive and significant effect on teacher performance in SMA Negeri in Kolaka District. This indicates that the higher the competence of a teacher, the teacher's performance will increase because of the high responsibility for the work assigned to him, (2) the facility has a positive and significant effect on the teacher's performance in the Senior High School in Kolaka District. This indicates that there is a tendency that the availability of complete learning facilities will assist or support the achievement of teacher performance, and (3) the motivation has a positive and significant effect on teacher performance in SMA Kolaka Regency. This shows that if a teacher has a high work motivation, then the teacher will do the job hard, diligent, and with high dedication so that will be achieved maximum results.